A descriptive analysis of classified Nordic disabled sit-skiers during the Nordic World Championships 2013 - Schillinger, F.; Rapp, A.; Hakkarainen, A.; Linnamo, V.; Lindinger, S. J. (Sciene and nordic skiing III, 2016)
In Paralympic sit-skiing athletes with different impairments compete within the same class. To ensure fair competitions there is a classification that considers the athletes` impairment and functional capability. Based on this classification, athletes are grouped into five classes with a corresponding percentage system (Pemot et al. 2011). The level of the impairment affects biomechanical as well as physiological requirements to achieve adequate forward propulsion. While in non-disabled Nordic skiing the scientific research is rather extensive, in disabled skiers such scientific work is rare. The aim of this study therefore was to get an impression of how different athletes with different levels of impairment perform in a competition. The initiator of the project was the International Paralympic Committee (IPC) with the request to improve classification process in Nordic sit-skiing. They initiated a video data collection with the requirement to capture athletes of both gender during a sit-skiing race at different sections of the competition course. Furthermore there is the idea to create a data pool with video files, available for coaches, classifiers and researchers to enable them to use the data for individual purposes.